SISTEM INFORMASI PELAYANAN EKONOMI PEMBANGUNAN PADA KELURAHAN LANDASAN ULIN SELATAN KECAMATAN LIANG ANGGANG KOTA BANJARBARU - Rozaq, Abdul; Alfiyannor, Muhammad; Ekaputri, Wanda Hanan; Hardinto, Raden Kelik (P3M Politeknik Negeri Banjarmasin, 2022)
Community services are carried out computerized so that services can be better. The purpose of this study is to reveal problems, design and build an information system for the development of economic services in the South Landasan Ulin sub-district, Liang Anggang sub-district, Banjarbaru city, so that it can be implemented in the South Landasan Ulin sub-district to facilitate development economic services. This research uses qualitative research and uses the waterfall development method which consists of analysis, design, coding, testing, support and maintenance. This research can solve problems in the South Landasan Ulin sub-district, Liang Anggang sub-district, Banjarbaru city based on the web. This study resulted in the application of web-based development economic services in the South Landasan Ulin sub-district. This system contains a filling sheet for the preparation of a development economic letter in the South Landasan Ulin sub-district